The Right to Disconnect in Digital Workplaces: Maqāṣid al-Syarī'ah and Ijārah Perspectives - Zuhdan Ady Fataron (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2026)
Digital communication has become ubiquitous in contemporary professional life, systematically dissolving the boundary between work and private spheres and producing documented harms, including cognitive burnout, psychosocial fatigue, and digital enslavement. To address this structural exploitation, this study offers an original contribution by assessing the “Right to Disconnect” through the lens of Islamic labor law. Adopting a normative-doctrinal legal methodology, the study examines digital overwork using the Ijārah ‘alā al-A’māl contract (service lease), Maqāṣid al-Syarī'ah (objectives of Islamic law), and the Sadd al-Żarā’i’ maxim. The findings establish that managerial expectations of digital availability beyond contracted hours without equivalent compensation (ujrah al-miṡl) constitute Garar (uncertainty) and Ẓulm (injustice), thereby invalidating the principle of Maʿlūmiyyah in Islamic contract law. Furthermore, a worker’s refusal to respond outside formal hours cannot be classified as Nusyūz (insubordination), but constitutes a legitimate jurisprudential rejection of exploitation. The study concludes that institutionalizing the Right to Disconnect is a binding legal obligation (wajib li ghairihi) under Islamic economic law, and must be incorporated into Syarī'ah-compliant employment contracts (‘Aqd) and institutional standard operating procedures.